Energy Price Shocks and the Demand for Energy-Efficient Housing: Evidence from Russia's Invasion of Ukraine - Nils Braakmann; Bahadir Dursun; Harry Pickard (Institute of Labor Economics (IZA), 2023)
How do private consumers adapt to changes to energy prices, in particular do they invest in energy-saving measures? We study this question in the context of the rapid rise in energy prices caused by the Russian invasion of Ukraine in February 2022 and the demand for energy efficiency in the UK housing market. We find that the housing market barely reacted to a 60% increase in the price of energy. This finding holds in multiple contexts and across various robustness checks. Supplementary survey evidence suggests that people believe the energy price increases are temporary, not permanent.
Keywords: Q35; Q41; Q51; R31; 330; gas prices; energy efficiency; property markets